Worker’s Teaching and Development - Stancikas, Edmundas Regimundas (Ekonomika, 2001)
Developed countries are going in new quality level, wich is calling information society. That society have to be ready for new condition, certainly to apprehend everyone individual and all society improvement.Worker’s teaching and development importance, because determine large hall population and here is formed another different worker’s ripeness quality. In our country companys are orientate in no perspective personnel teaching policy. Suggest to use perfect systematic teaching model, which connected with estimation extension of the all teaching phase.